Clinical implications of bile cultures obtained during pancreatoduodenectomy: a cohort study and meta-analysis. Issue 7 (July 2021) - Groen, Jesse V.; Droogh, Daphne H.M.; de Boer, Mark G.J.; van Asten, Suzanne A.V.; van Prehn, Joffrey; Inderson, Akin; Vahrmeijer, Alexander L.; Bonsing, Bert A.; Mieog, J. Sven D.
Abstract: Background: The association between intraoperative bile cultures and infectious complications after pancreatoduodenectomy remains unclear. This cohort study and meta-analysis aimed to determine the predictive role of intraoperative bile cultures in abdominal infectious complications after pancreatoduodenectomy. Methods: The cohort study included 114 patients undergoing pancreatoduodenectomy. Regression analyses were used to estimate the odds to develop an organ space infection (OSI) or isolated OSI (OSIs without a simultaneous complication potentially contaminating the intraabdominal space) after a positive bile culture. A systematic review and meta-analysis was performed on abdominal infectious complications (Mantel-Haenszel fixed-effect model). Results: The positive bile culture rate was 61%, predominantly in patients after preoperative biliary drainage (98% vs 26%, p  < 0.001). OSIs occurred in 35 patients (31%) and isolated OSIs in nine patients (8%) and were not associated with positive bile cultures (OSIs: odds ratio = 0.6, 95% CI = 0.25–1.23, isolated OSIs: odds ratio = 0.77, 95% CI = 0.20–3.04). In the meta-analysis, 15 studies reporting on 2047 patients showed no association between positive bile cultures and abdominal infectious complications (pooled odds ratio = 1.3, 95% CI = 0.98–1.65). Conclusion: Given the rare occurrence of isolated OSIs and similar odds for patients with positive and negative bile cultures to develop abdominal infectious complications, routine performance of bile cultures should be reconsidered.